The Role of the Ummi Method in Developing Al-Qur’an Reading Proficiency: An Evaluation of Tilawah and Tahfizh Achievements in Integrated Islamic Schools - Muhammad Kamaluddin; Ahmad Sukandar (CV. Media Digital Publikasi Indonesia, 2026)
This descriptive qualitative study analyzes the role and effectiveness of the Ummi Method in developing Al-Qur’an reading proficiency (Tilawah and Tahfizh) among students at SMPIT Ibnu Khaldun Lembang, an Integrated Islamic School. The study evaluates student achievement against the school's systematic curriculum targets over one semester. Data were collected through sustained observation, in-depth interviews with teachers and students, and systematic documentation analysis of Munaqasyah and Jilid progression records. Findings indicate that while the majority of students met or exceeded targets, significant variability in proficiency exists, primarily linked to students' initial motivation and rigorous group conditioning. The method’s success is critically dependent on teachers’ spiritual competence (Ruhiyah), pedagogical methodology, and conducive learning management. The study recommends continuous spiritual and professional development for teachers and intensive motivational programs to ensure optimal, holistic student outcomes.